2020
DOI: 10.1136/bmjopen-2020-037513
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution and types of breast lesions among Afghan women diagnosed by fine needle aspiration cytology (FNAC) at a tertiary care centre in Afghanistan: a descriptive cross-sectional study

Abstract: ObjectivesIn Afghanistan, breast diseases are a common reason for women to visit hospitals. This is the first study in Afghanistan aimed to describe the age distribution and types of breast diseases among patients diagnosed by fine needle aspiration cytology.DesignDescriptive cross-sectional study.SettingFrench Medical Institute for Mothers and Children, Kabul, Afghanistan.ParticipantsThe study included 650 patients with breast lesions between 1 April 2015 and 1 April 2019.ResultsThe mean age of diagnosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In these areas, patients suffer from poor hygiene, poor transport facilities to health centres and limited medical knowledge in self-assessment [ 3 6 ]. There are only sparse data on breast cancer in Afghanistan [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, patients suffer from poor hygiene, poor transport facilities to health centres and limited medical knowledge in self-assessment [ 3 6 ]. There are only sparse data on breast cancer in Afghanistan [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 32 Furthermore, studies of BC in Afghan women suggest that the mean age of diagnosis is younger than the global average, emphasizing the importance of instituting cancer awareness programs for a wide demographic of Afghan women. 23 The mean participant age in our study was 35 years, nearing the Turkish recommended breast cancer screening start age of 40 years, further emphasizing the need for rapid institution of BC awareness initiatives in this population.…”
Section: Discussionmentioning
confidence: 65%
“…Formal data regarding breast cancer diagnoses in Afghanistan are severely limited, but a recent study found a mean age at breast cancer diagnosis of only 43 years old, significantly lower than global average of approximately 62 years old. 23 , 24 Therefore, an assessment of cancer awareness specifically among Afghan refugees is critically needed. The present study begins to address this urgent need by investigating the level of awareness of BC among Afghan refugees in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Afghanistan between 2015 and 2019 from 650 patients with breast lesions, 24% were diagnosed with breast cancer when cytology tests were performed, with an average age of cancer diagnosis being 43.6 years and the earliest age being 20 years. 34 Breast cancer has been more common among Arab women over the last 26 years, with 45,980 new cases and 20,623 deaths reported in 2016 in the region. 35 Aggressive breast tumors were reported 19,755 in Sri Lankans in the years 2001–10.…”
Section: Resultsmentioning
confidence: 99%